Youth Empowerment in the Integration Program of Stunting Prevalence Reduction in East Java during Covid-19 Pandemic: A Document Review - Anjaswarni, Tri; Winarni, Sri; Hardy, Syaifoel; Kuswulandari, Shanti (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: More than 25% of East Java regencies and cities had stunting prevalence rates higher than the national figure. The involvement of the youths to reduce stunting is important in helping to overcome this national health problem. This study aimed to identify areas in East Java that have stunting prevalence rates above the national rate and assisted in the preparation of a program called the Youth Empowerment for Stunting Reduction Program (YESREP).Methods: This descriptive study used document review by PRISMA stages. At the initial stage, 453 documents were filtered from Google Scholar (n=29), Pubmed (n=12), SagePub (n=20), Semantic Scholar (n=6), others (n =136), while the remaining (n=260) were discarded. The search keywords were ’youth empowerment’, ‘stunting’, and ‘Covid-19’. The inclusion criteria were stunting cases, youth empowerment, and the Covid-19 pandemic. The documents screened were journals with quantitative, qualitative, document review methods, year of publication:2017-2022, focusing on youth empowerment and stunting, and in English or Indonesian languages. The tool used for the final document selection used PICOT model.Results: Youth empowerment was one of the effective methods in reducing the stunting prevalence. However, training programs, orientation, continuity, guidance, and follow-up are needed. The challenges were in funds, time, and readiness of the human resources involved in the implementation of YESREP.Conclusion: YESREP as a concept, was effective in reducing stunting prevalence, but still have some limitations. This study recommends conducting experimental research through a pilot project,